The summer the Archduke died essays on wars and warriors - Rubin, Louis Decimus, 1923- (University of Missouri Press, 2008)
"Writer and literary scholar Rubin turns his thoughts to World War I and its aftermath, a subject of lifelong fascination for him. Topics range from tactics used at the naval battle of Jutland, to critiques of revisionist histories of Winston Churchill, to the war's impact on literature"--Provided by publisher.